Pemahaman Ayat-Ayat Al-Qur’an dan Sikap Multikultural pada Mahasiswa Muslim di Perguruan Tinggi Kalimantan Barat - Musti'ah, Musti'ah; Suherdiyanto, Suherdiyanto (Jurnal Pendidikan Agama Islam Al-Thariqah, 2025)
The purpose of this study was to investigate two important factors: the understanding of the verses of the Qur'an and the multicultural attitudes of Muslim students (BI) in Pontianak and their correlation. This study applied a quantitative research design through the distribution of questionnaires (online) to 130 of 200 Moslems students at a private university in Pontianak, West Kalimantan. Then, the data were analyzed descriptively and non-parametrically. The results of this study revealed that BI students had a high understanding of the verses of the Qur'an and multicultural attitudes and the two variables had a very close positive relationship based on the results of the Kendall Tau Correlation analysis (τ = 0.856, p < 0.001). The results of this study indicated that Islamic Religious Education could be an effective pathway in building multicultural attitudes, even without direct intercultural contact. In contrast to previous multiculturalism studies that generally highlight differences between religious groups, this study explores multicultural attitudes among Muslim students from various tribes/ethnicities (Malay, Javanese, Dayak, Madurese) within the same religion, which is still relatively rarely studied. Furthermore, the theoretical and empirical implications of this research are also discussed in this article